Japanese case of Charcot–Marie–Tooth disease type 2Z with severe retinitis pigmentosa. Issue 5 (22nd August 2022) - Nomura, Emi; Tadokoro, Koh; Sasaki, Ryo; Nakata, Yumi; Nakano, Yumiko; Yunoki, Taijun; Takemoto, Mami; Morihara, Ryuta; Ando, Masahiro; Takashima, Hiroshi; Yamashita, Toru
Abstract: Charcot–Marie–Tooth disease type 2Z (CMT2Z) shows highly variable clinical features. We report the first Japanese CMT2Z patient with a c.754C>T (p.R252W) substitution of the MORC2 gene, complicating severe retinitis pigmentosa. The MORC2 mutants were involved in a decrease in cell survival through induction of apoptosis. Thus, the MORC2 mutation might be involved in the degeneration of photoreceptors and the development of retinitis pigmentosa.